Synergistic Combination of Facile Thiol-Maleimide Derivatization and Supramolecular Solvent-Based Microextraction for UHPLC–HRMS Analysis of Glutathione in Biofluids - Yan, Mengmeng; Gao, Feng; Chen, Meng; Hu, Qi; Yang, Yuqin; Chen, Kedian; Wang, Penglong; Lei, Haimin; Ma, Qiang (Frontiers in Chemistry, 2021)
Glutathione (GSH) is the most abundant non-protein thiol in biofluids, enabling diverse physiological functions. Among the proposed methods for GSH detection, ultra-high-performance liquid chromatography (UHPLC) coupled with high-resolution mass spectrometry (HRMS) has the advantages of high sensitivity and efficiency. In this study, a novel analytical method was developed for the determination of GSH using supramolecular solvent (SUPRAS)-based dispersive liquid-liquid microextraction (DLLME) and UHPLC-HRMS. N-Laurylmaleimide was dissolved in tetrahydrofuran, which served three functions: (1) precipitate the proteins present in the biofluid sample, (2) provide a reaction environment for derivatization, and (3) enable the use of SUPRAS as the dispersing agent. Critical parameters were optimized based on single factor testing and response surface methodology. The established method was validated in terms of linearity, accuracy, precision, and successful quantitative analysis of GSH in saliva, urine, and plasma samples. Experimental results showed that SUPRAS as an extraction solvent was particularly suitable for the extraction of GSH from complex matrices. The current study provides a useful tool for accurate measurements of GSH concentrations, which could potentially be used for clinical diagnostics.